Independent voting in bogotá: a critical view (2010)
When it comes to electoral affairs, Bogotá has been characterized throughout the last two decades as a singular voting district in Colombia where independent voting prevails. This article criticizes this depiction of Bogotá’s electoral reality by analyzing three fallacies which have facilitated the expansion of such representation: (i) Bogotá’s urban voting, is relatively homogeneous and compact when compared to the rest of the country, (ii) Voters of Bogotá cast an independent type of vote whereas countryside districts cast a patronage type of vote, (iii) The prevailing status of independent voting in Bogotá confirms the elimination of traditional bi-partisan practices.